Meningkatkan Soft Skills Siswa Melalui Pemanfaatan Aplikasi Canva di SMK Al Muhajirin - Ardiansyah, Muhammad Risky (Jurnal Pengabdian Masyarakat, 2024)
The background to this community service activity stems from the importance of soft skills in facing the challenges of an increasingly dynamic world of work. In the context of vocational education such as at Al Muhajirin Vocational School, apart from technical skills (hard skills) taught through the formal curriculum, soft skills such as creativity, communication and teamwork are important assets to support students' readiness to enter the world of work. The focus of this community service is to provide training on using the Canva application to Al Muhajirin Vocational School students, which is designed to improve creativity, visual communication skills and collaboration skills. This research uses a qualitative approach with a participatory action research research design. This research was conducted with the aim of understanding how the use of the Canva application can improve the soft skills of Al Muhajirin Vocational School students. The importance of developing innovative and creative soft skills to increase student motivation and help achieve learning goals as well as building interaction and knowledge in creating interesting learning media. This training exists to meet the need to utilize technology as an innovative and interesting learning medium. One application that is easy to use is Canva. The Canva application is a learning medium that can be used remotely, so it can be said to be a creative, innovative and collaborative learning medium, so it can be said to be very helpful in the teaching and learning process.